UV and Near-IR triggered release from polymeric nanoparticles - Fomina, Nadezda (2010)
A new light-sensitive polymer containing multiple light-sensitive triggering groups along the backbone and incorporating a quinone-methide self-immolative moiety was developed and formulated into nanoparticles encapsulating a model dye Nile Red. Triggered burst-release of the payload upon irradiation and subsequent degradation of the nanoparticles was observed. This system is designed to be versatile where the triggering group can be sensitive to a number of wavelengths.